Computational modeling and simulation of gas focused liquid micro-sheets. (July 2021) - Belšak, Grega; Bajt, Saša; Šarler, Božidar
Abstract: The purpose of this work is to numerically evaluate the behavior of microscopic gas-focused liquid sheets in terms of material properties, nozzle structure and operating conditions used for experiments in spectroscopy and scattering where a short optical path is required. The numerical simulations are presented of a gas flow focusing nozzle, capable of producing a stream consisting of a sequence of perpendicular micrometre thin liquid sheets. The nozzle structure consists of a central circular capillary for delivery of the liquid and two circular capillaries that provide the focusing gas flow in a converging direction from opposite directions. High velocity impinging gas jets accelerate and form a thin elliptically shaped liquid sheet which contracts downstream and eventually forms a similar shaped sheet in the plane perpendicular to the primary sheet. The process repeats further downstream with another contraction, forming the tertiary sheet, existing now in the same plane as the primary sheet. This produces a liquid jet in form of a series of perpendicular micrometre thin liquid sheets. Three dimensional conservation equations of mass, energy and momentum for a compressible two-phase system are solved with a finite volume approach and an algebraic volume of fluid method. The influence of liquid viscosity, density, surface tension, nozzle layout variation as well as gas and liquid operating parameters on the evolution of the primary liquid sheet is elaborated. The parameter space of six flow characterizing dimensionless numbers is explored in the following ranges: Reynolds gas number 64–130, Reynolds liquid number 122–620, Weber number 23–803, ratio of liquid to gas mass flow rate 16–58, viscosity ratio 26–79, and density ratio 4807–7221. The layout of the primary sheet is given in terms of sheet thickness, width and length. The results show minor effect of dynamic viscosity, a moderate effect of density and a dominant role of the surface tension. The liquid sheet shape is sensitive to the variation of gas and liquid flow rates as well as the nozzle's structure width and the angle between the liquid delivery and the focusing gas capillaries.